English Language Proficiency and its Impact on Professional Identity, Operational Skills, and Gender Dynamics among Police Cadets in Greece (Journal of Advanced Research in Social Sciences, 2024)
This study explores the impact of English language proficiency on professional identity, operational skills, and gender dynamics among cadets at the Hellenic Police Officers School in Greece. It addresses three main research questions: 1) How does English proficiency influence cadets' professional identity? 2) What is the relationship between English proficiency and operational skills in international policing? 3) How does gender intersect with language proficiency in handling gender-sensitive cases, particularly femicide? Employing a mixed-methods approach, data were gathered from 102 cadets across various proficiency levels, complemented by qualitative insights from questionnaires, interviews, and reflective essays. The study identifies a strong correlation between advanced English proficiency and both professional confidence and operational effectiveness, underscoring the importance of language skills in international collaborations and gender-sensitive policing. Two case studies illustrate these findings: one highlights the role of language proficiency in international counter-terrorism collaboration, and the other emphasizes its significance in the gender-sensitive handling of femicide cases. These examples demonstrate the practical application of advanced English skills in critical law enforcement scenarios, reinforcing the need for tailored English as a Second Language (ESL) programs. Such programs, designed with attention to gender-specific learning styles and operational contexts, are crucial for preparing officers for effective cross-border collaboration and sensitive crime management. This research advocates for a learner-centered ESL curriculum development, aligning with societal needs and policy implications, and calls for further investigation in diverse settings. By emphasizing the intersection of language proficiency with professional and operational efficiency, this study contributes valuable insights to ESL education, sociolinguistics theory, and law enforcement training practices, highlighting the transformative potential of specialized language training in global law enforcement.